PENGARUH SUBSTITUSI KEDELAI DENGAN BIJI LAMTORO (LEUCAENA LEUCOCEPHALA) PADA TEMPE TERHADAP KANDUNGAN GIZI DAN TOTAL FENOL UNTUK PENDERITA DIABETES MELITUS - Febri Adrian Milenio (2022)
Diabetes mellitus is a disease characterized by the presence of free radicals in the body. Phenol is one type of antioxidant to overcome free radicals. Lamtoro seeds are a source of phenol. The general objective of this study was to analyze the effect of substitution of lamtoro seeds on the proximate content, total phenol and organoleptic properties of soybean tempe and determine the selected formula. The research method used is experimental with a one-factor Complete Randomized Design (CRD) with two repetitions and four treatment levels with different ratios of lamtoro seeds and soybeans, namely F0 (0:100), F1 (40:60), F2 (50:50), and F3 (60:40). The ANOVA results showed that the substitution of lamtoro seeds had a significant effect on the water, protein, fat, carbohydrates, ash, crude fiber and phenol content in tempeh (p<0,05). The results of organoleptic analysis showed that the substitution of lamtoro seeds had a significant effect on the panelists' preference for color and texture parameters (p<0,05). F3 became the selected formula with 66,17% water content, 12,16% protein, 5,85% fat, 13,7% carbohydrate, 1,36% ash, 4,45% crude fiber, and 0,77 mg phenol.